Clinical and Demographic Factors Associated with Receiving an Opioid Prescription following Admission to the Pediatric Intensive Care Unit - Amy L. Holley; Trevor A. Hall; Ben Orwoll; Anna C. Wilson; Eleanor A. J. Battison; Denae Clohessy; Cydni N. Williams (MDPI AG, 2022)
Opioids are commonly used to treat pain in the pediatric intensive care unit (PICU), and many children receive opioid prescription(s) at discharge. The frequency of opioid prescriptions at discharge and associations with individual characteristics and clinical factors are unknown. This study aimed to identify (1) the number of children who receive an opioid prescription at PICU discharge and (2) the demographic and clinical factors associated with receiving an opioid prescription. Data were collected via the electronic medical record. The sample was 3345 children (birth to 18 years) admitted to the PICU and discharged to home or an inpatient rehabilitation setting. In total, 23.7% of children were prescribed an opioid at discharge. There were group differences in who received opioid prescriptions (yes/no) related to PICU diagnosis, length of hospital stay, number of days on mechanical ventilation, number of previous hospitalizations, organ dysfunction score, and admission type (surgical versus non-surgical). Binary logistic regression models examined predictors of opioid prescription at discharge for the total sample and diagnostic subgroups. Older age and surgical admission type were the most consistent predictors of receiving an opioid prescription. Future research should examine prescription usage patterns and how use of opioids is associated with pain and functional outcomes over time.